PREY PREFERENCE AND PREDATORY BEHAVIOR OF Aurantilaria aurantiaca (MOLLUSCA: GASTROPODA: FASCIOLARIIDAE) - de Meirelles, Carlos Augusto Oliveira; Matthews-Cascon, Helena (Arquivos de Ciências do Mar, 2017)
Fasciolariid species are predators that prey on other gastropods and bivalves. They usually break prey shell to reach its soft parts. In this study, prey species that Aurantilaria aurantiaca consumes at Pacheco Beach (Ceará State, Northeast Brazil) and its prey preference in laboratory conditions were determined. Prey species observed were Pisania pusio, Tegula viridula and Stramonita brasiliensis. Prey preference experiment was performed placing one individual of Aurantilaria aurantiaca and one individual of each prey species in a 5 liters tank. It lasted 60 days and was replicated 10 times. Handling time of predation on each prey was measured by placing one predator with one prey into separate plastic containers in an 80 liters tank. Observations were made every 2 hours over a 30-day period. Aurantilaria aurantiaca showed preference for Stramonita brasiliensis, which presented the shortest handling time. Pisania pusio and Tegula viridula didn’t show statistical significant results (p = 0.7235 e 0.2499 respectively). Aurantilaria aurantiaca presented 2 main predatory strategies: direct prey shell penetration and asphyxiating process. No damaged prey shells were observed. The predator showed a generalist predatory behavior. Prey handling time variations demonstrated that Aurantilaria aurantiaca predation act involved a training process.